The Effect of The Blended Learning Model Assisted by The Google Classroom Application on The Science Learning Outcomes - Islamiyati, Dian; Bahtiar, Bahtiar; Zohri, Muhammad (Indonesian Journal of STEM Education, 2022)
This study aims to examine the effect of the blended learning model assisted by Google Classroom on students’ science learning outcomes. The research employed a quasi-experimental design with a pretest-posttest control group. The sample consisted of 31 students in the experimental class and 30 students in the control class, selected using simple random sampling. Data were collected using a multiple-choice test. The results showed that the average post-test score of the experimental class (86.58) was higher than that of the control class (65.20). Hypothesis testing using an independent t-test indicated that tcount (10.36) > ttable (2.00) at a 5% significance level. These findings indicate that the blended learning model assisted by Google Classroom has a significant effect on students’ science learning outcomes. These findings indicate that the blended learning model assisted by Google Classroom is effective in improving students’ science learning outcomes.